Girls School Dropout Rate in Malawi: a Threat to National Development - Fayiah, Moses; Khomera, Sphiwe (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to explore the key factors contributing to girls' school dropout rates in Malawi and its impacts on national development. It seeks to identify the root causes, understand the socio-economic implications, and propose potential solutions that could mitigate the issue. Methods and Materials: The study utilizes secondary data from various sources, including United Nations reports, Malawian statistical data, newspaper articles, and conference proceedings related to female education in Malawi. Data were systematically collected and synthesized to provide a comprehensive view of the causes and consequences of female dropout rates in both primary and secondary education. Findings: The findings indicate that the primary causes of school dropout among girls in Malawi are poverty, early marriage, long distances to school, teenage pregnancy, domestic responsibilities, and gender-based violence. These factors significantly contribute to the disproportionate dropout rates between girls and boys. The study highlights that the high dropout rates among girls negatively affect national development by limiting women's participation in leadership roles and the economy. Conclusion: Girls’ dropout from school presents a critical challenge to Malawi's socio-economic development. While policies have been implemented, such as the National Education Sector Plan and readmission policies for school-aged mothers, more targeted interventions are necessary. The study recommends improving school infrastructure, providing scholarships, and initiating nationwide awareness campaigns to encourage female education.